Reconstrucción de la curva de carga eléctrica residencial a partir de selección muestral usando sensado comprimido - Andrade Montoya, Paúl Alexander (2017)
The demand response (DR), search to provide quality service, that allows to reduce significantly the costs and to guarantee the security of the network. Therefore, it is necessary to make an adequate estimate of the load curve, considering that an intelligent measurement system has been implemented to obtain the demand data. In an Advanced Measurement Infrastructure (AMI), there is the possibility of failures or malicious attacks that may disrupt the exchange of information between the electrical company and end users, causing the loss of data and hasn't complete information of load profiles. In this article presents techniques that allow the reconstruction of the load curve with a minimum amount of data. For this, a comparative analysis is performed between different algorithms that use a matrix mathematical model, based on the compressed sensing theory. In addition, to know which is the best option, a reconstruction error calculation is performed using a percentage of the mean square difference, considering the original signal and the reconstructed signal.